2017
DOI: 10.1186/s12882-017-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of bone biopsies from the iliac crest, the tibial bone, and the lumbar spine

Abstract: BackgroundPatients with an impaired renal function show a high incidence of bone and mineral disturbances. These ‘chronic kidney disease – mineral and bone disorders’ (CKD-MBD) range from high turnover osteoporosis to adynamic bone disease. Currently, the histomorphometric analysis of a bone biopsy taken from the iliac crest is viewed as the gold standard for CKD-MBD subtype differentiation. However, the clinical relevance of such a biopsy is questionable since iliac crest fractures are an extremely rare findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Despite being the gold standard for diagnosing the underlying pathology in CKD‐MBD (known as ROD), it is performed in few specialised centres, and its processing and analysis require significant expertise and thus is seldom performed in routine clinical practice. It is also limited by its ability to only provide a measure of bone quality at a single site, and studies have shown significant discrepancies in the underlying ROD when samples have been concomitantly taken from the iliac crest, lumbar vertebra and proximal tibia . Furthermore, two or more bone biopsies are required to assess response to therapy, and no studies have demonstrated bone biopsy findings that provide fracture prediction.…”
Section: Bone Health In Patients With Chronic Kidney Disease–mineral mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being the gold standard for diagnosing the underlying pathology in CKD‐MBD (known as ROD), it is performed in few specialised centres, and its processing and analysis require significant expertise and thus is seldom performed in routine clinical practice. It is also limited by its ability to only provide a measure of bone quality at a single site, and studies have shown significant discrepancies in the underlying ROD when samples have been concomitantly taken from the iliac crest, lumbar vertebra and proximal tibia . Furthermore, two or more bone biopsies are required to assess response to therapy, and no studies have demonstrated bone biopsy findings that provide fracture prediction.…”
Section: Bone Health In Patients With Chronic Kidney Disease–mineral mentioning
confidence: 99%
“…It is also limited by its ability to only provide a measure of bone quality at a single site, and studies have shown significant discrepancies in the underlying ROD when samples have been concomitantly taken from the iliac crest, lumbar vertebra and proximal tibia. 32,33 Furthermore, two or more bone biopsies are required to assess response to therapy, and no studies have demonstrated bone biopsy findings that provide fracture prediction. The initial 2009 KDIGO guidelines necessitated a bone biopsy in patients with CKD-MBD prior to consideration of anti-resorptive therapy given theoretical concerns of inducing or worsening ABD in patients with already low bone-turnover states.…”
Section: Diagnosis and Investigationsmentioning
confidence: 99%
“…Iliac crest biopsies have also documented preserved trabecular bone in PHPT [6]. However, studies comparing cadaver biopsies from the LS and iliac crest have shown significant discrepancy between the two sites, suggesting that iliac crest histomorphometry may not accurately reflect lumbar spine microarchitecture [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find studies that evaluated whether clinical conditions, such as CKD, can determine the predominance of a specific pattern (rod × plate). While previous studies compared the various sites using only microtomography, Hiller et al (2017) performed this analysis using histomorphometry and microCT of the iliac crest, proximal tibia, and lumbar vertebra, wherein they observed variations in BV/TV and no correlation between them. The authors highlighted intra-individual and inter-individual differences.…”
Section: Discussionmentioning
confidence: 99%